Translatio iudicii no direito processual civil brasileiro - Sato, Priscila Kei (2010)
After ample discussion in the Italian doctrine and case law, on June 19, 2009, Act n. 69 was passed in Italy and in its article 59 attempted to fill the gap about the connection between administrative and ordinary jurisdictions. The legislator did not adopt the translatio iudicii principle as it had been conceived for the cases in which the lack of jurisdiction is acknowledged, as per art 50 of the Italian Civil Procedure Code. In Brazil, both the translatio iudicii principle and resumption of procedure are part of the civil procedural system, although such terms are not expressly adopted. Procedures are resumed and the files are sent to competent court in cases in which relative and absolute lack of jurisdiction has been declared. In the first case, all former acts remain valid (including intermediate court orders) and in the second intermediate court orders are considered null and void while all other acts remain in effect. However, the existing rules under the Brazilian legislation are insufficient to cover every concrete case. Analyzing our case law, one observes that, often, the chosen path is dismissal without prejudice, instead of adopting the translatio iudicii and procedure resumption, based on unconstitutional grounds that infringe the principles of access to justice and reasonable duration of procedures. On the other hand, there is no thorough study about procedural effects (e.g., perpetuatio iurisdicionis and lis pendens) of the acts performed before the unqualified court. This study aims at analyzing the applicability of translatio iudicii and proceeding resumption under the Brazilian Civil Procedural Law on the evidence of constitutional principles; procedural and material effects of the acts performed before the unqualified court; and to propose solutions other than the ones provided in our case law